Snakebite is Under Appreciated: Appraisal of Burden from West Africa. - Abdulrazaq G Habib; Andreas Kuznik; Muhammad Hamza; Maryam I Abdullahi; Basheer A Chedi; Jean-Philippe Chippaux; David A Warrell (Public Library of Science (PLoS), 2015)
BACKGROUND:Snakebite envenoming (SBE) is a major problem in rural areas of West Africa (WA). Compared to other Neglected Tropical Diseases (NTD), the public health burden of SBE has not been well characterized. We estimated the impact of snakebite mortality and morbidity using the Disability Adjusted Life Years (DALYs) metrics for 16 countries in WA. METHODS:We used the reported annual number of SB deaths and mean age at time of SB and converted these into years of life lost (YLL). Similarly, the years of life lived with disability (YLD) were estimated by multiplying the number of amputations by the respective disability weight of 0.13. RESULTS:In WA, the annual cases of SB mortality and amputations ranged from 24 (95% Confidence Interval: 19-29) and 28 (17-48) respectively in Guinea-Bissau with the highest estimates of 1927 (1529-2333) and 2368 (1506-4043) respectively in Nigeria. We calculated that the annual DALYs associated with a SB death ranged from 1550 DALYs (95%CI: 1227-1873 DALYs) in Guinea Bissau to 124,484 DALYs (95%CI: 98,773-150,712 DALYs) in Nigeria. The annual DALYs associated with amputation for the two countries were 149 DALYs (95%CI: 91-256 DALYs) and 12,621 DALYs (95%CI: 8027-21,549 DALYs) respectively. The total burden of SBE was estimated at 319,874 DALYs (95% CI: 248,357-402,654 DALYs) in the 16 countries in WA. These estimates are similar, and in some instances even higher, than for other NTDs encountered in WA (e.g., Buruli ulcer, Echinococcosis, Intestinal Nematode Infections, Leishmaniasis, Onchocerchiasis, Trachoma and Trypanosomiasis) as reported in the Global Burden of Diseases 2010 (GBD). CONCLUSIONS:The public health burden of SBE in WA is very substantial and similar to other more widely recognized NTDs. Efforts and funding commensurate with its burden should be made available for the control of snakebite in the sub-region.